Gamified Financialization in The Light of Islamic Behavioural Economics: Psychological and Ethical Dimensions of Speculative Behaviour in Virtual Asset Markets - Muhammad Said; Andi Kiki Patmawati; Minhajuddin Madi; Sry Muliyani; Andi Dinul Islam Firdaus (International Journal of Islamic Business and Economics (IJIBEC), 2025)
The phenomenon of gamification in virtual asset trading has transformed investment behavior into an activity driven by psychological mechanisms such as Fear of Missing Out (FOMO), overconfidence, herding behavior, and loss aversion. This study aims to analyze how gamified design in digital trading platforms fosters speculative behavior that violates Islamic ethical principles such as tawazun (balance between risk and benefit), gharar (excessive uncertainty), and maisir (gambling). Employing a qualitative approach through a systematic literature review of academic journals and industry reports, the study finds that features such as real-time notifications, leaderboards, and reward animations increase trading frequency, risk-taking, and market volatility. These dynamics create asymmetry in risk and reward, disproportionately harming low-literacy retail investors. The study concludes that digital financial innovation must be balanced with ethical regulation, financial literacy, and maslahah-based design to ensure market justice and sustainability in line with Islamic economic principles. This research contributes to strengthening Islamic financial ethics and integrating maqasid al-shariah values into modern digital finance innovation